The Exposure Effect to Some Air Pollutants as a Result of Specimens' Preservation for the Employees of Two Museums in Baghdad City - Ezz Aldeen, Shaymaa A.; Fleeh, Nada Abdul Rahman (Iraqi Journal of Science, 2026)
The study aims to evaluate the health effects of exposure to air pollutants by applying hematological and biochemical analysis to (39) employees (15 male and 24 female) at the Iraqi National Museum (M1) and Natural History Museum (M2) in Baghdad City during the summer and winter seasons, who were exposed to air pollution, to determine the extent to which pollutants resulting from using of specific materials in cleaning, fogging, and preservation of museums' specimens, affect these employees' blood. A temtop device was used to measure the main indoor environmental parameters in these museums, particularly (total volatile organic compounds (TVOC), formaldehyde (HCHO), and particulate matter (PM2.5 and PM10). Basic hematological parameters: hematocrit (HCT), hemoglobin concentration (HGB), Red Blood Cell count (RBC), White Blood Cell count (WBC), Platelets count PLT, liver function, and renal function were measured. The test was performed after the volunteer employees completed a questionnaire about their age, sex, duration time of work, daily exposure, and other details. For the hematological test, although the average concentration of HGB level for M2 is less than in M1, the average concentration of it was within the normal range, and so for WBCs, RBCs, and PLT counts were within the normal range in the two museums for both seasons. Regarding the HCT level, the average concentration in winter was 40.52 ± 0.77 for M1 and 36.72 ± 1.34 for M2, meaning M2 results were below the normal range during the winter. As for biochemical analysis (liver function), the AST, ALT, and ALP levels were within the normal range in the two museums for both seasons, except that the ALP level in M2 was higher than in M1. In addition, renal function results showed that urea and uric acid levels in M2 were lower than in M1. In contrast, the creatinine level was higher in M2 than in M1, knowing that the levels of urea, creatinine, and uric acid were within the normal range in the two museums for both seasons.